Fairness Aspect in the Paroan System in the Mangar Society - Martoyo Martoyo; Abdul Jabbar (Indonesian Journal of Law and Islamic Law (IJLIL), 2023)
This research was conducted on the Mangar society who have a system of cooperation in the form of "paroan agreements" which can be categorized as creative in drafting and implementing agreements. The social system of the Mangar society is quite interesting to explore because in the midst of a very exploitative agricultural and livestock management system, the Mangar society remains consistent in upholding justice by placing the position of farm laborers in a balanced way both in terms of roles and the distribution of benefits from managing the farm. The research method used in this research is qualitative research or field research. The results of this study indicate: (1) The paroan agreement form of the Mangar society is an oral agreement; (2) Implementation of the paroan agreement begins with an agreement between the two parties, namely the land owner and the manager. Then the implementation starts from clearing the land to harvesting; (3) The meaning of justice in the paroan agreement can be seen from: first, equal opportunity to help each other and obtain welfare between the parties. Second, there is a balance of rights and obligations. Third, there is appreciation based on the principle of mutual need. Fourth, in the distribution of profits based on mutually agreed agreements.